Monocentric cities, endogenous agglomeration, and unemployment disparities - Ulrich Zierahn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The literature on the wage curve provides considerable evidence in favor of a negative relationship between unemployment and wages. It is thus often seen as a refutation of the Harris-Todaro model, who point to a positive relationship. This paper shows that both strands of literature are special cases of a more general approach by combining a New Economic Geography model with monocentric cities and efficiency wages. Whether the relationship is positive or negative depends on the transportation costs between the cities and commuting costs within them. The model helps explain whether and under which conditions the agglomeration of economic activity is associated with higher unemployment and why controls for agglomeration should be included in wage curve regressions.
Keywords: R12; R14; R23; 330; New Economic Geography; Urban Economics; Efficiency Wages; Unemployment; Disparities; Regional Migration; Lohnkurve; Stadtstruktur; Agglomerationseffekt; Regionale Arbeitslosigkeit; Regionale Disparität; Effizienzlohn; Binnenwanderung; Theorie